Collaborative Agents for Modeling Traffic Regulation Systems - Bhouri, N.; Balbo, F.; Pinson, S.; Tlig, M. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
The development of surface public transportation networks is a major issue in terms of ecology, economy and society. Their quality in term of punctuality and passengers services(regularity between buses) should be improved. To do so, cities often use regulation systems at junctions that grant priority to buses. However, most of them hardly take into account both public transport vehicles such as buses and private vehicle traffic. This paper proposes a bimodal urban traffic control strategy based on a multi-agent model. The objective is to improve global traffic, to reduce bus delays and to improve bus regularity in congested areas of the network. In our approach, traffic regulation is obtained thanks to communication, collaboration and negotiation between heterogeneous agents. We tested our strategy on a complex network of nine junctions. The results of the simulation are presented.